Gender and Ethnic Diversity, and Economic Value Added: Evidence from Government-Linked Companies / Michele Merara ... [et al.] - Merara ,, Michele; Janang, Jennifer Tunga; Bujang, Imarine (Universiti Teknologi MARA Cawangan Sarawak, 2021)
Board diversity was further emphasized in the revised Malaysian Code ofCorporate Governance (MCCG) 2017, as this can allow for more board effectiveness in constructive debates and better decisions. With this recommended deliverable, the code believes that companies should perform and will be more equipped to face the ever-changing business environment and challenges. This study examines the influence of boardroom diversityon corporate performance using Government-Linked Companies (GLCs) in Malaysia as units of analysis. The study used secondary data of publicly listed GLCs in Malaysia for seven years (2012 to 2018). We used gender and ethnicity to proxy for boardroom diversity while economic value added (EVA) represents the company’s performance. We also used panel data multiple regression to analyze the data. After controlling for firm size and firm age, the empirical results revealed that board ethnicity is negatively and significantly related to firms’ economic performance. Board gender, however, provides insignificant results. We also find the firm size to be significant and positively related to EVA. This preliminary result on board composition requires further research on how Malaysian GLCs can address the MCCG’s recommended governance compliance, particularly on the monitoring roles of the board on firm performance.